Alleviating malnutrition through agriculture in Bangladesh: biofortification and diversification as sustainable solutions - Roos, Nanna; Bouis, Howarth E.; Hazzan, Nazmul; Kabir, Khandaker Aminul (International Food Policy Research Institute, 2004)
This volume presents the proceedings of a workshop titled “Alleviating Micronutrient Malnutrition through Agriculture in Bangladesh: Biofortification and Diversification as Long-Term, Sustainable Solutions.” The premise of the presentations and discussions was the urgent need to create a new paradigm for agriculture—where agriculture’s vital role in providing nutrients for human populations is assimilated into research, investment, and policy decisions by the agriculture sector as well as the health and nutrition sectors. The workshop comprised two sessions. The first, held at the BRAC Centre for Development Management, Rajendrapur, Gazipur, on April 22–23, 2002, was attended by an interdisciplinary group of approximately 40 participants involved in research and applied activities to improve agricultural production and human health and nutrition in Bangladesh. The group discussed various topics linking agriculture with nutrition and health and developed recommendations for policies and follow-up actions. These discussions were summarized and the recommendations presented at a one-day closing session held at the Sasakawa Auditorium at ICDDR,B in Dhaka on April 24.